TOPONIMI BADAN USAHA DI ERA OTSUS PAPUA: Analisis Nilai Ekonomi, Sosial-Budaya, dan Politik di Kota Jayapura - Marit, Elisabeth Lenny (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2017)
This paper aims to disclouse about naming or name offering on the kind of corporate types containing elements of the language unit the form of categories sub noun, adjective, verb, pronoun, and the same type. Naming or name reference it is known by the term toponimi (form the name). In the field of scientific study called the antroponimi study.The fact that the currently emerging corporate names that are likely to be free to give a name to fit the character and local based in the Papua special autonomy. Affirmative and specificities of the Special Autonomy Law for Papua tend to open up spaces of democracy for the Papua Origin to vote and determine the lexicon a lexicon or word choice- the name of the corresponding value of the philosophical, sociological, and political.In perspective of Linguistics, language functions that in fact can reveal the meaning and symbol behind the name of the type of corporate ownership about a world economy (business) which are available in the understanding as a reality.This paper takes a sample corporate names in the city of Jayapura, Papua Province. In principle, this paper with Linguistics and Economics elaborated through the phenomenological philosophical approach. These approaches can be explored as a whole as a complex socio-cultural phenomenon. In the era of Corporation Toponimi Papua Special Autonomy to have an influence get analysis , that is (1) the economic value, (2) socio-cultural value, and (3) politic value.